Structural Validity and Reliability of the Indonesian Version of Self-Leadership - Gunawan, Gianti; Kadiyono, Anissa Lestari; Raspati, Fasya Adisa (Universitas Gadjah Mada, 2025)
Introduction/Main Objectives: This study aims to provide a self-assessment of self-leadership among the Indonesian workforce, contributing to a deeper understanding of self-leadership at the individual level and supporting personal growth and development. Background Problems: As self-leadership increasingly becomes recognized as a key factor in organizational success, there is a need for an assessment tool adapted to the Indonesian context. This study addresses the gap by developing and validating an instrument that measures self-leadership's cognitive and behavioral processes, including behavioral, motivational, and constructive thought patterns. Novelty: This study pioneers the cultural adaptation and validation of a self-leadership assessment tool for the Indonesian workforce. By utilizing a validated self-assessment tool with theoretical and practical implications, this study promotes personal and organizational improvement. Research Methods: Data were analyzed using Structural Equation Modeling (SEM), with confirmatory factor analysis (CFA) and reliability testing applied to evaluate the psychometric properties of the instrument. Finding/ Results: The instrument demonstrated a high level of reliability, with a Cronbach's Alpha coefficient of 0.933, indicating strong internal consistency. The CFA confirmed the factor structure, with factor loadings exceeding 0.3, affirming the construct validity of the tool. Conclusion: The Indonesian version of the Self-Leadership Questionnaire (SLQ) is a valid and reliable instrument for measuring self-leadership. This study offers a novel contribution by being the first to culturally adapt and validate a self-leadership measure for the Indonesian context and filling a gap in current leadership research.